UNSUR-UNSUR PEMBANGUNAN DALAM PENGELOLAAN PENGAIRAN * - Saadah, Saadah; Darma, Rahim; Mahyuddin, Mahyuddin (Universitas Muhammdaiyah Surakarta, 2012)
The research was conducted in Pinrang district with the aim to analyze the potential and problems in irrigation management. Data were collected by interview method on the P3A advisers and FGD to the members of six elected P3A. Data were analyzed descriptively about resources, organizations, and the rules of irrigation management. The results showed that the organization of P3A less functional because there is no coordination between P3A and GP3A, including the duplication guidance of District offices of Irrigation and Agriculture, the utilization of water resources is inefficient because of silting in the secondary channel, water gate set freely by farmers, some tertiary channels damaged or turned off by the farmers, many farmers who make a shortcut channel, lack of watergate regulator; there are no sanctions imposed for who make shortcut and turn off channels. The members of P3A should be involved on every policy process making in the field of irrigation.